Tipologi Motif Cap Tangan Prasejarah di Leang Uhallie, Kabupaten Bone, Sulawesi Selatan - Leihitu, Irsyad (UI Scholars Hub, 2016)
This article discusses the typology of a hand stencil pattern cave painting located in Leang Uhallie, Bone district, South Sulawesi. Irving Rouse’s taxonomy classification methods were used to find the typology of the hand stencil pattern. This study shows that there are three forms of hand stencil with 21 variants. This typologycal study of the hand stencil also shows the dominant and the unique pattern form of Leang Uhallie.